Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
Step-by-step explanation:
1) x +y = 3
Subtract 'x' from both sides
y = -x + 3
2) x - 3y = 12
Subtract 'x' form both sides.
-3y = -x + 12
Divide the entire equation by (-3)
[tex]\dfrac{-3y}{-3}=\dfrac{-x}{-3}+\dfrac{12}{-3}\\\\\\y = \dfrac{1}{3}x-4[/tex]
3) 5x + 2y = 10
Subtract 5x from both sides
2y = -5x + 10
Divide the entire equation by 2
[tex]\dfrac{2y}{2}=\dfrac{-5x}{2}+\dfrac{10}{2}\\\\\\y = \dfrac{-5}{2}x + 5[/tex]
4) y = 6x + (1/3)
It is already in y =mx +b form
5)
[tex]y=\dfrac{1}{x}*x-15\\\\\\y = 1-15\\\\y = -14\\\\y=0x -14[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.